Respuesta :
Step-by-step explanation:
A. y= -x+5(equation no. 1)
x+2y=2(equation no. 2)
On substituting 1 in 2, we get,
x+2(-x+5)=2
x-2x+10=2
-x+10=2
x=8
Put x=8 in any of the equations and find y
B. y=3x+5(equation no. 1)
4y-x=-2(equation no. 2)
On substituting 1 in,we get,
4(3x+5)-x=-2
12x+20-x=-2
11x+20=-2
11x=-22
x=-2
Put x=-2 in any of the equations and find y
Step-by-step explanation:
A. x + 2(-x + 5) = 2
x + -2x + 10 = 2
-x = -8
x = 8
y= -8 + 5 = -3
B. 4( 3x + 5) - x = -2
12x + 20 - x = -2
11x = -22
x = -2
y = 3× -2 + 5
y = -5 + 5
y =0